Risk factors of pregnancy in adolescence and the aspects that influence it (Research, Society and Development, 2022)
Adolescence is a period marked by physical, biological and psychological changes; it is, therefore, a phase of adjustments for adult life, where an unplanned pregnancy at that time can have serious consequences in the young woman's life. To demonstrate these facts, the study starts from a qualitative-quantitative bibliographic review, seeking to present the theme about the risks of teenage pregnancy (for the pregnant woman and the baby) and the consequences of pregnancy in the life of the young woman, correlating with the data. quantitative data provided by SINASC (Information System on Live Births), and the scientific production found in SciELO, Virtual Health Library (BVS) and Lilacs. It can be seen that teenage pregnancy tends to bring numerous consequences and various risks for the teenager, both in the biological and social context. It is highlighted the impossibility of completing adolescence, the lack of preparation to be a mother, family and psychological conflicts, lack of commitment to her new condition; low schooling; future professional commitment, impossibility of self-sufficiency, financial independence and others, in addition to the risks to the baby, which are very clear and punctual. It was concluded that a well-done prenatal care makes all the difference for mother and baby, especially in adolescents. Informing young people about forms of prevention, both unwanted pregnancy and STIs are avoided, demonstrating to them what an unplanned pregnancy can have an impact on their lives.